Os regimentos dos ouvidores de comarca na América portuguesa, séculos XVII e XVIII: esboço de análise - Yamê Galdino de Paiva (Nuevo mundo - Mundos Nuevos, 2017)
The regimentos (instructions) corresponded to legal instruments designed to serve as a model for the good administration of local populations. As judges appointed by the king, the ouvidores should have such provisions in the jurisdictions in which they were to serve (comarcas). However, these documents had a sporadic and irregular character. The aim of this article is to make a brief analysis of the regimentos received by the ouvidores of Brazil from the second half of the 17th to the end of the 18th century, highlighting their elaboration and recurrence, points of similarity and eventual changes over time. In addition, it seeks to frame the regimentos as instruments used by the Portuguese crown to rule its domains and, therefore, overcome distances.